Africa Rising, a Narrative for Life Expectancy Gains? Evidence from a Health Production Function - Donald Salami; Ahmed Nabil Shaaban; Maria do Rosário Oliveira Martins (Ubiquity Press, 2019)
Background: The narrative of Africa Rising has increasingly been called into scrutiny, not just as a debate for economic growth and development, but also as a possible link to the surge in life expectancy on the continent. Theoretically, an increase in economic development tends to result in an increase in public health spending and subsequent better health outcomes. Objective: This paper examines the contribution of economic development and other social determinants to the health status of the African continent and to provide evidence on whether the increase in life expectancy of the past two decades can be largely attributed to the Africa Rising narrative. Methods: We estimated an empirical health production function, with life expectancy gains as the output of the health care system, and various socio-economic, environmental and lifestyle factors as contributory factors. We fitted a generalized least squares model, using panel data from 52 African countries for the period 1995-2014. Findings: The estimation shows that while increases in health care spending contributed to life expectancy gains, urbanization rates and improved water access were the major drivers of life expectancy gains with substantially larger impacts in the past two decades. Conclusions: Overall, the results provide an evidence base for iterating the need to prioritize increasing funding and examine more critically how to improve the efficiency of health spending. It also illustrates potential gains that can be achieved from an inclusive health policy agenda with a broader range of social and economic development issues.